Churg–Strauss presenting as acute coronary syndrome: sometimes it's zebras. (13th April 2011) - Kakouros, Nicholaos; Bastiaenen, Rachel; Kourliouros, Antonios; Anderson, Lisa
Abstract : A 53-year-old patient presented to our institution with troponin-positive chest pain and new-onset peripheral oedema. A week prior, while abroad, he had developed visual disturbances and fever in conjunction with an elevated troponin. Coronary angiography had revealed minor coronary artery disease and he was treated for acute coronary syndrome and occult infection. On arrival to our coronary care unit, further review elicited a history of recently diagnosed and worsening severity asthma with nasal polyposis. A mononeuritis and a vasculitic rash were noted and blood screen showed hypereosinophilia and immunoglobulin E (IgE) elevation. A clinical diagnosis of Churg–Strauss syndrome was made and the patient was treated urgently and successfully with immunosuppressants. The case illustrates a fulminant presentation mode of this rare vasculitis and the importance of seeking a unifying diagnosis in cases presenting with apparently disparate symptoms and findings.